Greenhouse gas mitigation potential of Alternate Wetting and Drying for rice production at national scale - A modeling case study for the Philippines - Kraus, David; Werner, Christian R.; Janz, Baldur; Klatt, Steffen; Sander, Björn Ole; Wassmann, Reiner; Kiese, Ralf; Butterbach-Bahl, Klaus (American Geophysical Union, 2022)
Worldwide, rice production contributes about 10% of total greenhouse gas (GHG) emissions from the agricultural sector, mainly due to CH4 emissions from continuously flooded fields. Alternate Wetting and Drying (AWD) is a promising crop technology for mitigating CH4 emissions and reducing the irrigation water currently being applied in many of the world's top rice-producing countries. However, decreased emissions of CH4 may be partially counterbalanced by increased N2O emissions. In this case study for the Philippines, the national mitigation potential of AWD is explored using the process-based biogeochemical model LandscapeDNDC. Simulated mean annual CH4 emissions under conventional rice production for the time period 2000–2011 are estimated as 1,180 ± 163 Gg CH4 yr−1. During the cropping season, this is about +16% higher than a former estimate using emission factors. Scenario simulations of nationwide introduction of AWD in irrigated landscapes suggest a considerable decrease in CH4 emissions by −23%, while N2O emissions are only increased by +8%. Irrespective of field management, at national scale, the radiative forcing of irrigated rice production is always dominated by CH4 (>95%). The reduction potential of GHG emissions depends on, for example, number of crops per year, residue management, amount of applied irrigation water, and sand content. Seasonal weather conditions also play an important role since the mitigation potential of AWD is almost double as high in dry as compared to wet seasons. Furthermore, this study demonstrates the importance of temporal continuity, considering off-season emissions and the long-term development of GHG emissions across multiple years.